(untitled) (Annals of Medical Research, 2024)
Aim: It is aimed to evaluate our patients who were operated for Chiari type 1 malformation with the help of literature and to contribute to the literature. Materials and Methods: 14 patients who were operated on for Chiari type 1 malformation diagnosis between 2012 and 2022 were retrospectively examined. Results: The mean age of our 14 patients included in the study was 36.39 (5 ​​months - 59 years). The postoperative intensive care unit stay was 2.57 days, and the total stay until discharge was 10.93 days on average. The mean cerebellar tonsil herniation in our patients was 13.36 mm. The female/male ratio was 1. Syringomyelia was detected in 78.6% of our patients. 13 of the 14 patients were discharged in good health, and 1 patient died in the postoperative period. Conclusion: In patients with Chiari type 1 malformation, the presence of syringomyelia in addition to tonsillar herniation has been noted as a valuable parameter in the decision to operate. Although the most common condition in symptomatic patients is headache, it should be kept in mind that atypical symptoms may also occur. Patients who have undergone surgery for Chiari type 1 malformation should be closely monitored postoperatively for possible complications.